Salivary anti-cyclic citrullinated peptide as a screening tool for rheumatoid arthritis - Nazanin Mortazavi,; Nafiseh Abdolahi,; Mohsen Saeidi,; Mohammad Ali Vakili,; Pouria Mohebrad, (Archives of Rheumatology, 2023)
Objectives: This study aims to evaluate the sensitivity and specificity of salivary anti-cyclic citrullinated peptide 3 (anti-CCP3) for the early diagnosis of rheumatoid arthritis. Patients and methods: Between June 2017 and April 2019, a total of 63 patients with rheumatoid arthritis (10 males, 53 females; mean age: 50.4±9.5 years; range, 27 to 74 years) and 49 healthy controls (8 males, 41 females; mean age: 49.3±9.3 years; range 27 to 67 years) were included. Salivary samples were collected by passive drooling. Anti-cyclic citrullinated peptide analyses of salivary and serum samples were performed. Results: The mean polyclonal immunoglobulin (Ig)G-IgA anti-CCP3 salivary levels were significantly different in patients (149.2±134.2) compared to healthy controls (28.5±23.9). The mean polyclonal IgG-IgA anti-CCP3 serum levels were measured as 254.0±169.5 in patients and 3.8±3.6 in healthy individuals. The diagnostic accuracy analysis of salivary IgG-IgA anti-CCP3 results in an area under the curve (AUC) of 0.818, as well as 91.84% specificity and 61.90% sensitivity. Conclusion: Salivary anti-CCP3 may be considered as an additional screening test for rheumatoid arthritis.